Evolutionary and Molecular Aspects of Plastid Endosymbioses - Oborník, Miroslav; Füssy, Zoltán (Biomolecules, 2021)
Plastids are membrane-bound organelles that bestow phototrophic abilities to eukaryotes [...].
Keywords: Symbiosis; Plastids; plastidy; biologická evoluce; Biological Evolution; symbióza